THE EFFECTIVENESS OF ICT-BASED PROBLEM BASED LEARNING IN IMPROVING HOTS - FEHABUTAR, DALIANA; JATMIKO, BUDI (Inovasi Pendidikan Fisika, 2019)
AbstractThis study aimed to describe the effectiveness of ICT-based Problem Based Learning in improving HOTS learners. This type of research is pre experimental design consisting of two experimental class with the same treatment. The analysis technique used is the paired t test to test differences in the pre-test and post-test, n-gain analysis to look at the criteria for the increase in value, as well as independent t test to see the average gain consistency both experimental classes. ICT-based PBL models is effective when the value of the post-test was higher than the pre-test, the average value of n-gain minimal medium category, and the average gain of both the experimental class is no different. The conclusion of the research is ICT-based Problem Based Learning is effective in improving HOTS.Keywords: Problem Based Learning, ICT, HOTS. Abstrak Penelitian ini bertujuan untuk mendeskripsikan keefektifan Problem Based Learning berbasis ICT dalam meningkatkan HOTS peserta didik. Jenis penelitian yang digunakan adalah pre experimental design yang terdiri dari dua kelas eksperimen dengan perlakuan yang sama. Teknik analisis yang digunakan adalah uji t berpasangan untuk menguji perbedaan nilai pre-test dan post-test, analisis n-gain untuk melihat kriteria peningkatan nilai, serta uji t independent untuk melihat kekonsistenan rata-rata gain kedua kelas eksperimen. Model PBL berbasis ICT dikatakan efektif apabila nilai post-test lebih tinggi daripada nilai pre-test, nilai rata-rata n-gain minimal berkategori sedang, dan kedua rata-rata gain kedua kelas eksperimen tidak ada beda. Kesimpulan yang diperoleh dari hasil penelitian dan analisis, model PBL berbasis ICT efektif dalam meningkatkan HOTS Peserta didik.Kata kunci: Problem Based Learning, Berbasis ICT, HOTS.